Controlled human malaria infection studies: insights into recent advances and key immunological and ethical implementation lessons - Ogwang, Rodney; Adan, Mohamed; Bejon, Philip; Kapulu, Melissa C. (Frontiers in Immunology, 2025)
Controlled human infection studies offer a unique opportunity to study the efficacy of novel interventions, mechanisms of infection and disease, as well as determine correlates of protection that may underpin the development of novel interventions. Controlled human malaria infection (CHMI) studies supported the clinical development of the first malaria vaccines (i.e. RTSS/AS01 and R21/Matrix-M). The CHMI model accurately predicted efficacy of these vaccines and accelerated their clinical development. In addition to vaccine development, over the last decade CHMI studies have supported the advancement of drugs, monoclonal antibodies (mAbs) and been instrumental in characterising immunity to malaria by unravelling immunological and innate mechanisms that may mediate protection. Here, we briefly review the history and rationale of the available falciparum malaria CHMI models. We highlight key applications and lessons learned from CHMI studies conducted in naïve and endemic populations with respect to immunological advances, discoveries in therapeutic targets such as mAbs, and transferring of the models from high income to low- and middle-income settings.